The effects of hypertension on aortic valve stenosis. Issue 3 (14th February 2005) - Bermejo, J
Abstract : Hypertension not only can modify the exploratory findings of aortic stenosis, but may also interfere with the assessment of severity, and even have an impact on patient outcome